Patient-reported outcomes, physician-reported toxicities, and treatment outcomes in a modern cohort of patients with sinonasal cancer treated using proton beam therapy. (July 2020) - Pasalic, Dario; Ludmir, Ethan B.; Allen, Pamela K.; Thaker, Nikhil G.; Chapman, Bhavana V.; Hanna, Ehab Y.; Su, Shirley Y.; Ferrarotto, Renata; Glisson, Bonnie S.; Reddy, Jay P.; Brandon Gunn, G.; Fuller, C. David; et al.
Highlights: Prospective toxicity analysis of patients treated using proton beam therapy (PBT). PBT was associated with only one acute grade 3 neurologic toxicity that resolved. There were no late grade 3–4 neurologic toxicities. Patient-reported outcomes worsened from baseline to the acute and subacute period. Patient-reported outcomes did not differ from baseline to chronic follow-up. Abstract: Background and purpose: To report physician-assessed toxicities (PATs) and patient-reported outcomes (PROs) in a prospective cohort of patients treated using proton beam therapy (PBT). Methods and materials: From 2011 to 2019, PBT-treated patients with a sinonasal malignancy were enrolled with a primary endpoint of toxicity assessment. PATs and PROs were assessed at baseline, acute (during PBT), subacute (within 90 days after PBT), and chronic time points. PATs were graded with the Common Terminology Criteria for Adverse Events V4.0. PROs were assessed with the Xerostomia-Related Quality-of-Life Scale (XeQoLS), MD Anderson Dysphagia Inventory (MDADI), and Functional Assessment of Cancer Therapy (FACT). PRO changes from baseline to follow-up were defined as significantly different based on a paired t -test plus a minimal clinically important difference. Results: Sixty-four patients had a median follow-up time of 33 months (interquartile range: 10–52 months). The most common histology was olfactory neuroblastoma (28%) and most patients had T4 disease (46%). One acute G3 neurologic PAT (blurred vision) resolved, and no late G3–4 neurologic PATs were observed. Feeding tube placement occurred in 6% of patients. No significant changes were noted in PROs from baseline to the chronic period. Significant worsening from baseline was noted in the XeQoLS acute-subacute physical functioning, pain, personal/psychological distress, and social function; acute-subacute MDADI physical function; and acute-subacute FACT head/neck subscale. The 3-year local control, disease-free survival, and overall survival rates were 88%, 76%, and 82%, respectively. Conclusions: We demonstrate low grade ≥3 toxicity and encouraging disease outcomes with PBT. PROs suggest significant changes in the acute-subacute period but no chronic sequelae.